Rapid Quantitative Analysis of Multiple Explosive Compound Classes on a Single Instrument via Flow‐Injection Analysis Tandem Mass Spectrometry12. Issue 1 (24th May 2018) - Ostrinskaya, Alla; Kunz, Roderick R.; Clark, Michelle; Kingsborough, Richard P.; Ong, Ta‐Hsuan; Deneault, Sandra
Abstract: A flow‐injection analysis tandem mass spectrometry (FIA MSMS) method was developed for rapid quantitative analysis of 10 different inorganic and organic explosives. Performance is optimized by tailoring the ionization method (APCI/ESI), de‐clustering potentials, and collision energies for each specific analyte. In doing so, a single instrument can be used to detect urea nitrate, potassium chlorate, 2, 4, 6‐trinitrotoluene, 2, 4, 6‐trinitrophenylmethylnitramine, triacetone triperoxide, hexamethylene triperoxide diamine, pentaerythritol tetranitrate, 1, 3, 5‐trinitroperhydro‐1, 3, 5‐triazine, nitroglycerin, and octohy‐dro‐1, 3, 5, 7‐tetranitro‐1, 3, 5, 7‐tetrazocine with sensitivities all in the picogram per milliliter range. In conclusion, FIA APCI/ESI MSMS is a fast (<1 min/sample), sensitive (~pg/mL LOQ), and precise (intraday RSD < 10%) method for trace explosive detection that can play an important role in criminal and attributional forensics, counterterrorism, and environmental protection areas, and has the potential to augment or replace several of the existing explosive detection methods.